2006
DOI: 10.1007/s10750-005-1007-6
|View full text |Cite
|
Sign up to set email alerts
|

Surface Rheology Parameters of Source-Specific Surfactant Films as Indicators of Organic Matter Dynamics

Abstract: The paper contains the results of natural film experiments carried out on inland and coastal waters in the Dead Vistula catchment area and mouth during 2000-2002, using the integrated Langmuir troughWilhelmy plate system. The static film parameters result from the generalized scaling procedures applied to the surface pressure-area isotherms. They appear to reflect in a quantitative and sensitive way the film composition (A lim , M w , E isoth ), film solubility and the miscibility of its components (via R, DS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…The third pool consists of less than 1% of the total OM in the ocean, but it is very labile and so represents a large C flux (Hansell et al, 2009). We suggest that this fraction, generally close in space and time to areas of high productivity, is also the most rheologically active, both in the SML (Pogorzelski et al, 2005) and in the bulk phase (Jenkinson and Sun, 2010;Jenkinson et al, 2015).…”
Section: Om In the Oceansmentioning
confidence: 88%
See 1 more Smart Citation
“…The third pool consists of less than 1% of the total OM in the ocean, but it is very labile and so represents a large C flux (Hansell et al, 2009). We suggest that this fraction, generally close in space and time to areas of high productivity, is also the most rheologically active, both in the SML (Pogorzelski et al, 2005) and in the bulk phase (Jenkinson and Sun, 2010;Jenkinson et al, 2015).…”
Section: Om In the Oceansmentioning
confidence: 88%
“…Concerning vertical molecular diffusion Pogorzelski (2001), Pogorzelski and Kogut (2001) and Pogorzelski et al (2005), reviewing previous work, calculated molecular mass M W from plots of surface pressure, Δτ 2D vs. t for short (t → 0) and long (t → ∞) times, and also calculated diffusion coefficient D as if it had been composed of monomers rather than polymeric clusters. Values of M w scattered widely from 2 to 166 kDa, with a typical value of 50 kDa.…”
Section: D Dilational Rheological Properties Of the Surface Filmmentioning
confidence: 99%
“…For a wind‐sheared water surface, reasonable choices for the turbulence scales are the water friction velocity u * and the roughness length z o = a u * 2 /g, where a is a constant of the order of 1400 [e.g., Craig and Banner , 1994]. For a wind speed of 5 m/s, u * ∼ 1 cm/s and z o ∼ 1 cm; so using a value of E ∼ O (10 mN/m) as typical of a filmed area of ocean [e.g., Pogorzelski et al , 2006] yields β * ∼ O (10). This high value of β * suggests (based on Figure 5a) a thermal slick contrast near its maximum value.…”
Section: Analogy Between the Effects Of Slicks In Sar And Ir Imagerymentioning
confidence: 99%
“…How strong an underlying motion is needed to break up a film? It is known that the occurrence of slicks diminishes rapidly as the wind increases from near calm to a speed of ∼5 m/s [ Romano , 1996; Pogorzelski et al , 2006]. This behavior is usually attributed to a break‐up and dispersal by Langmuir circulation (Figure 1), but detailed observations of the dispersion of natural slicks by Langmuir circulation appear to be lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Hunter and Liss [3] suggested that surface film is a gelatinous matrix, with molecules supported at the interface by inter and intramolecular interactions. Some authors [10] emphasize the multicomponent character of natural surfactant films and the consequent complications in attempting to predict interfacial elastic properties due to the diverse chemical makeup of such films.…”
Section: Introductionmentioning
confidence: 99%